ORGANIZATIONAL CITIZENSHIP BEHAVIOR DALAM PERSPEKTIF ISLAM (APLIKASI TAKWA) - Farida Elmi (MIX: JURNAL ILMIAH MANAJEMEN, 2019)
The aim of this research is to describe and understand Organizational Citizenship Behavior (OCB) in Islamic perspective (application of piety) of ITL Trisakti employees in Jakarta. This is a study case research with a qualitative approach. The data were collected through observation and interview. The informants of this study are employees of   ITL Trisakti. This thesis is the effort to study scientifically the meaning of OCB in Islamic perspective, and how is piety implemented. Good comprehension of the subjects over piety and its internalization has shaped and formed OCB. Regarding OCB of ITL Trisakti employees, it can be inferred that of all dimension of altruism; civic virtue, advocating high moral standards, and removal of harm, merely all are observable within the employees. Piety can be a discourse in educational institution research and contributes to achieve organizational goals